Emotional Intelligence and Leadership Effectiveness: Navigating Decisions, Team Dynamics, and Organizational Success - Giri, Yam Nath (Journal of Global Economy, Business and Finance, 2025)
Emotional Intelligence (EI) has become an essential factor in leadership effectiveness, significantly influencing decision - making, team dynamics, and overall success in organizational contexts. This study explores how leaders with high emotional intelligence manage their own emotions and those of others, enhancing decision - making processes, fostering team cohesion, and achieving better organizational outcomes. By examining key EI components such as self - awareness, self - regulation, empathy, and social skills, this research highlights how emotionally intelligent leaders improve team performance, foster collaboration, and drive organizational success. The findings emphasize the importance of incorporating EI in leadership development to address complex challenges in modern organizations.